Effect of Amendments on Soil Charge Characteristics in Sub-Optimal Dryland of Aceh Besar, Indonesia - Sufardi Sufardi; Teti Arabia; Khairullah Khairullah; Tri Chairina (JOURNAL OF TROPICAL SOILS, 2026)
Soil colloids play a critical role in controlling chemical behavior, particularly in tropical sub-optimal drylands dominated by variable-charge soils. However, information on the comparative effects of organic and inorganic amendments on soil charge characteristics across different soil orders remains limited. This study aimed to evaluate the effects of compost, biochar, CaCO3, and Superphosphate fertilizer (SP-36) on the charge characteristics of tropical dryland soils. Nine amendment combinations were applied to topsoil (0–20 cm) from Andisols (Saree), Inceptisols (Cucum), and Ultisols (Jantho), followed by incubation for 60 days at 25–27 °C under field capacity conditions. Soil charge parameters were analyzed before and after incubation. Results showed that amendment type and rate significantly affected soil charge characteristics, with responses varying among soil orders. Organic amendments (15–30 t ha-1) and SP-36 (2–4 t ha-1) decreased pH€  and significantly increased cation exchange capacity (CEC) and net negative charge, indicating improved soil reactivity. In contrast, CaCO3  increased pHo  and reduced negative charge. These findings support the strategic use of organic amendments to enhance soil fertility and sustainability.